STUDI SIFAT KIMIA, FUNGSIONAL, DAN DAYA CERNA PROTEIN TEPUNG KECAMBAH KACANG TUNGGAK (Vigna unguiculata (L.) Walp) - Nidya Elvira; Ni Wayan Wisaniyasa; Ni Made Indri Hapsari Arihantana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2019)
The purpose of this study was to determine the chemical, functional, and protein digestibility of cowpeasprout flour. This study was conducted using germination and without germination of cowpea, and eachtreatment was repeated three times. Cowpea flour and cowpea sprout flour were tested for chemicalproperties (moisture content, ash content, protein content, fat content, carbohydrate content, crude fibercontent), functional properties (water absorption, oil absorption, swelling volume, solubility,wettability) and protein digestibility. The germination of cowpea had a very significant effect onmoisture content, a significant effect on water absorption, swelling volume, solubility, wettability,protein content, and protein digestibility, and had no significant effect on oil absorption, ash content,fat content, carbohydrate content, and crude fiber content. The results showed that chemical propertiesof cowpea flour and cowpea sprout flour that is water content 4.96% and 2.6%, ash content 4.13% and4.15%, protein content 26.42% and 28.18%, fat content 1.44% and 1.24%, carbohydrate 63.04% and63.81%, crude fiber content 6.46% and 7.1%, functional properties of cowpea flour and cowpea sproutfloue that is water absorption 1.06 ml H2O/g solid and 1.39 ml H2O/g solid, oil absorption 1.44 ml oil/gsolid and 1.05 ml oil/g solid, swelling volume 7.08 ml/g and 6.37 ml/g, solubility 17.15% and 20.25%,wettability 420.60 seconds and 315.8 seconds, protein digestibility of cowpea flour and cowpea sproutflour were 45.28% and 48.45%.